A Global Perspective on the Outcomes of Surgical Decompression in Patients With Cervical Spondylotic Myelopathy: Results From the Prospective Multicenter AOSpine International Study on 479 Patients. Issue 17 (1st September 2015) - Fehlings, Michael G.; Ibrahim, Ahmed; Tetreault, Lindsay; Albanese, Vincenzo; Alvarado, Manuel; Arnold, Paul; Barbagallo, Giuseppe; Bartels, Ronald; Bolger, Ciaran; Defino, Helton; Kale, Shashank; Massicotte, Eric; et al.
Abstract : Study Design: Prospective, multicenter international cohort. Objective: To evaluate outcomes of surgical decompression for cervical spondylotic myelopathy (CSM) at a global level. Summary of Background Data: CSM is a degenerative spine disease and the most common cause of spinal cord dysfunction worldwide. Surgery is increasingly recommended as the preferred treatment strategy for CSM to improve neurological and functional status and quality of life. The outcomes of surgical intervention for CSM have never been evaluated at an international level. Methods: Between October 2007 and January 2011, 479 symptomatic patients with image evidence of CSM were enrolled in the prospective, multicenter AOSpine CSM-International study from 16 global sites. Preoperative and postoperative clinical status, functional impairment, and quality of life were evaluated using the modified Japanese Orthopaedic Assessment Scale, Nurick Scale, Neck Disability Index, and Short-Form-36v2. Preoperative and 12- and 24-month postoperative outcomes were compared using mixed-model analysis of covariance for repeated measurements. Results: The study cohort consisted of 310 males and 169 females, with a mean age of 56.37 ± 11.91 years. There were significant differences in age, etiology, and surgical approaches between the regions. At 24 months postoperatively, the mean modified Japanese Orthopaedic Assessment Scale score improved from 12.50 (95% confidence interval [CI], 12.24–12.76) to 14.90 (95% CI, 14.64–15.16); the Neck Disability Index improved from 36.38 (95% CI, 34.33–38.43) to 23.20 (95% CI, 21.24–25.15); and the SF36v2 Physical Component Score and Mental Composite Score improved from 34.28 (95% CI, 33.46–35.10) to 40.76 (95% CI, 39.71–41.81) and 39.45 (95% CI, 38.25–40.64) to 46.24 (95% CI, 44.94–47.55), respectively. The rate of neurological complications was 3.13%. Conclusion: Surgical decompression for CSM is safe and results in improved functional status and quality of life in patients around the world, irrespective of differences in medical systems and sociocultural determinants of health. Level of Evidence: 3 Abstract : Supplemental Digital Content is Available in the Text.This study evaluates clinical, functional, and quality-of-life outcomes in global patients with cervical spondylotic myelopathy undergoing surgical decompression. Surgery is associated with significant and sustainable improvements across all outcome measures in patients from around the world. Surgery is also a relatively safe procedure as rates of neurological complications are low.